A qualitative study on the impact of caring for an ambulatory individual with nonsense mutation Duchenne muscular dystrophy - Kate Williams; Ian Davidson; Mark Rance; Katharina Buesch; Sarah Acaster (SpringerOpen, 2021)
Abstract Background Duchenne muscular dystrophy is a rare genetic neuromuscular disorder, which can result in early death due to disease progression. Ataluren is indicated for the treatment of nonsense mutation Duchenne muscular dystrophy, in ambulatory individuals aged two years and older. This study explored the impact of caring for an ambulatory individual with nonsense mutation Duchenne muscular dystrophy, as well as the impact of treatment with ataluren on the caregiver experience, using retrospective recall. Methods Qualitative interviews were conducted with caregivers in the UK. Interviews were conducted by telephone, were recorded and transcribed. Data were analysed using thematic analysis and saturation was recorded. Results Ten interviews were conducted with parents of individuals aged 4-19 years. Caregivers reported proximal impacts (physical, emotional, time-related), and distal impacts (work, relationships, social life) of caring for their sons. The relationships between these impacts were illustrated in a conceptual model. Changes to the caregiver experience since initiation with their son's treatment were discussed. Conclusion Caring for an ambulatory individual with nonsense mutation Duchenne muscular dystrophy has a substantial multifaceted impact on caregivers. Treatments which have the potential to improve symptoms or delay progression, may also have a positive impact on the quality of life of caregivers.